PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL DENGAN PENDEKATAN GREEN EDUCATION UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VII SMP - Dewi Ajeng Martika; Bambang Sri Anggoro; Novian Riskiana Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by students’ difficulties in deeply understanding mathematical concepts, as indicated by a dominant procedural thinking pattern. This difficulty is reflected in students struggling to comprehend prerequisite materials, connect concepts with real-life contexts, restate concepts, distinguish examples from non-examples, and apply algorithms in problem-solving, along with limited relevance to daily life. The current learning approach does not emphasize meaningful conceptual understanding related to green education, nor has it incorporated innovative media such as digital comics in the learning process. This study aims to examine the development process, attractiveness, and effectiveness of digital comic media based on the Green Education approach in improving students’ mathematical conceptual understanding. The research employs the Research and Development (R&D) method using the 4D development model (Define, Design, Develop, and Disseminate). The results show that the digital comic media received an average feasibility score of 3.58 from media validation experts and 3.56 from content validation experts, both categorized as “Feasible.” Attractiveness testing on a small scale yielded a score of 3.35 and on a large scale 3.45, both classified as “Very Attractive.” Effectiveness evaluation using the Gain Index test resulted in a score of 0.67, categorized as “Moderate,” while the N-Gain score percentage was 67%, categorized as “Fairly Effective.